Prevalence of Active Play in Brazilian children and adolescents: an updated systematic review for the Brazil's Report Card - Greice Westphal; Igor Alisson Spagnol Pereira; Maria Luiza Costa Borim; Claudiana Marcela Siste Charal; Nelson Nardo Junior (Universidade Federal de Santa Catarina, 2021)
This paper is an update of the systematic review on Active Play published in 2018 by Mendes et al. This systematic review included studies published between 2018 and 2019. The search for potential articles was performed on the following electronic databases: Pubmed/Medline, Web of Science, Bireme, Scielo and Scopus. Initially, 471 papers met the eligibility criteria. However, after deeply analyzed, only two studies remained and were included in the present review. From these articles only one presented individual information on play activity among adolescents age (12-17 years) from Curitiba-PR and it reveals that 77,2% of them were physically active in their free time. The other study included was about the preferences for leisure activities among adolescents from Florianopolis-SC participants in two cross sectional studies in 2001 and 2011. It showed a significant reduction in the preferences for practicing physical activities, while the opposite occurs with sedentary activities like watching TV, playing video games, and using computers. These results along with the inconsistencies in benchmarks of the domain active play among countries involved in the Global Matrix 3.0 made clear the necessity of a standard definition and a proper tool to measure it.